Ultrasound‐guided multiple‐injection costotransverse block for mastectomy and primary reconstructive surgery. A study protocol. Issue 3 (5th January 2022) - Holm, Ulrik H. U.; Andersen, Christian H. S.; Hansen, Christian K.; Tanggaard, Katrine; Børglum, Jens; Nielsen, Martin Vedel
Abstract: Background: Post‐operative pain amelioration following breast cancer surgery is inconsistent. The novel multiple‐injection costotransverse block (MICB) mimics the thoracic paravertebral block by possible anaesthetising the ventral rami of the thoracic spinal nerves and the sympathetic trunk. Proof of concept has been determined in a cadaveric study and needs further clinical testing. Methods: This double‐blinded, randomised and placebo‐controlled study investigates the efficacy of the ultrasound‐guided MICB versus placebo in 36 patients undergoing unilateral mastectomy and primary subpectoral reconstruction surgery. Oral pre‐operative medicine is standardised for all patients. Active group is pre‐operatively administered MICB with three injections of each 10 ml of ropivacaine (5 mg/ml). The placebo group is pre‐operatively administered three injections of each 10 ml of saline (0.9%). Standard general anaesthesia is induced and 30 min before emergence 0.2 μg/kg total body weight sufentanil IV, 1 g of paracetamol IV and 4 mg of ondansetron IV (post‐operative nausea and vomiting, PONV, prophylaxis) will be administered. All patients are provided with a patient‐controlled analgesia pump with morphine. The primary aim is total morphine consumption in the first 24 post‐operative hours. Secondary aims are pain intensity, duration of the block, patient satisfaction, side effects, time to ambulation, time to discharge, and quality of recovery. Discussion: Recruitment began in November 2019 and is expected to finish ultimo 2021. Results are expected to be published in an international peer‐reviewed medical journal. The results will hopefully provide a substantial contribution to the knowledge of these new 'intertransverse process blocks' providing regional anaesthesia of the thoracic wall.